Predictive value of the inconsistency between the residual and post-PCI QFR for prognosis in PCI patients - Chen, Lihua; Zhong, Jiaxin; Hong, Ruijin; Chen, Yuxiang; Li, Beilei; Wang, Laicheng; Yan, Yuanming; Chen, Lianglong; Chen, Qin; Luo, Yukun (Frontiers in Cardiovascular Medicine, 2024)
Introduction To investigate the prognostic value of the consistency between the residual quantitative flow ratio (QFR) and postpercutaneous coronary intervention (PCI) QFR in patients undergoing revascularization. Methods This was a single-center, retrospective, observational study. All enrolled patients were divided into five groups according to the ΔQFR (defined as the value of the post-PCI QFR minus the residual QFR): (1) Overanticipated group; (2) Slightly overanticipated group; (3) Consistent group; (4) Slightly underanticipated group; and (5) Underanticipated group. The primary outcome was the 5-year target vessel failure (TVF). Results A total of 1373 patients were included in the final analysis. The pre-PCI QFR and post-PCI QFR were significantly different among the five groups. TVF within 5 years occurred in 189 patients in all the groups. The incidence of TVF was significantly greater in the underanticipated group than in the consistent group (P = 0.008), whereas no significant differences were found when comparing the underanticipated group with the other three groups. Restricted cubic spline regression analysis showed that the risk of TVF was nonlinearly related to the ΔQFR. A multivariate Cox regression model revealed that a ΔQFR≤ −0.1 was an independent risk factor for TVF. Conclusions The consistency between the residual QFR and post-PCI QFR may be associated with the long-term prognosis of patients. Patients whose post-PCI QFR is significantly lower than the residual QFR may be at greater risk of TVF. An aggressive PCI strategy for lesions is anticipated to have less functional benefit and may not result in a better clinical outcome.